Anti-hemogemonický pohľad na transformáciu v roku 1989 - Profant, Tomáš Imrich, 1983-
Recenzia knihy: The international political economy of transition. Neoliberal hegemony and Eastern Central Europe's transformationmore Eastern Central Europe's transformation.